Consolidation behaviour of the neutralisation spent pickle liquor (NSPL) sludge from steel works - N. N. Nik Daud,; H. R. Thomas,; S. Seetharam, (2010)
The disposal of industrial waste sludge at a landfill has become a global problem especially when dealing with high moisture content material. Neutralisation Spent Pickle Liquor (NSPL) sludge waste generated in steel industry has been categorized as one of the slurry wastes in geotechnical engineering and poses serious handling problem due to its high water content. The NSPL sludge waste is categorized as a high water content material with a low solid concentration.The main objective in this paper is present a study related to compressive behaviour of the NSPL sludge material under external load. A series of consolidation tests of different NSPL initial water content and load pressure using Rowe cell equipment were performed. The consolidation behaviour of the NSPL sludge was shown to be complex, especially during the initial stages of the loading process. For any given load increment, an instantaneous compression was observed but no pore water dissipation were detected. The coefficient of permeability was found to be very high during the first few minutes, i.e. in the range of 10-4 – 10-5 m/s, and reduces significantly to 10-10 m/s after the first 17 hours of the test. The compression behaviour of the sludge materials are directly related to their coefficient of permeability